Decontamination technologies for medicinal and aromatic plants: A review. Issue 3 (11th January 2022) - Rahmati, Edris; Khoshtaghaza, Mohammad Hadi; Banakar, Ahmad; Ebadi, Mohammad‐Taghi
Abstract: Microbial quality assurance has always been an important subject in the production, trade, and consumption of medicinal and aromatic plants (MAPs). Most MAPs have therapeutic and nutritional properties due to the presence of active substances such as essential oils, flavonoids, alkaloids, etc. However, MAPs can become infected with microorganisms due to poor hygienic conditions during cultivation and postharvest processes. This problem reduces the shelf life and effective ingredients of the product. To overcome these problems, several technologies such as using ethylene oxide gas, gamma irradiation, and steam heating have been used. However, these technologies have disadvantages such as the formation of toxic by‐products, low consumer acceptance, or may have a negative effect on the quality of MAPs. This requires a need for novel decontamination technology which can effectively reduce the biological contamination and minimize the food quality losses. In recent years, new technologies such as ozonation, cold plasma, ultraviolet, infrared, microwave, radiofrequency and combination of these technologies have been developed. In this review, biological contamination of MAPs and technologies used for their decontamination were studied. Also, the mechanism of inactivation of microorganisms and the efficacy of decontamination techniques on the qualitative and microbial characteristics of MAPs were investigated. Abstract : Medicinal and aromatic plants are often contaminated with biological contamination. Usage of novel technologies is different according to the type of product. Combined systems were suggested to be a promising technique for decontamination.